Modifications Greedy Best-first Search To Efficiency Memory of Pathfinding Algorithm In Hajjgame - FAJAR HARIADI (NIM: 23207132), AGUS
This paper describes the research conducted to improve the efficiency of memory usage algorithms pathfinding on interactive learning media in the form of 3-dimensional game, namely HajjGame. Modifications made is to reduce the number of nodes that must be checked at while agent running pathfinding algorithm. Modifications were made can contribute to the efficient use of memory used HajjGame.